The interrelationship between childhood obesity and vitamin D deficiency: a systematic review - Almhizai, Rheem A.; Alrehaili, Layan A.; Alzoum, Nora M.; Alhomood, Lujain S.; Alrowaitee, Norah T.; Alharbi, Amal N.; Alsayel, Lama T.; Alshedookhi, Amjad A.; Almukhtar Alshinqity, Khadijah M. (International Journal Of Community Medicine And Public Health, 2025)
Objective was to look into the connection between vitamin D deficiency (VDD) and childhood obesity. The 489 pertinent papers were found after a comprehensive search across four databases. Eight research finally met the requirements for inclusion after 262 full-text publications were screened, duplicates were eliminated using Rayyan QCRI, and relevance was assessed. A total of 1851 obese children from eight trials were included in our analysis; 919 (49.6%) of the patients were female. The prevalence of VDD among obese children ranged from 24.7% to 88.5%, with a total prevalence of 881 (47.6%). Taken together, results have indicated a significant association of obesity in childhood with VDD at high prevalence rates across populations and age groups. Despite receiving enough sunshine in some residential areas, obese children and adolescents have been reported to have low blood vitamin D levels, which reflects behavioral inputs like reduced outdoor activity that add to the VDD. The susceptibility seems to be enhanced by puberty and female gender, emphasizing the need for targeted intervention. Obese children and adolescents are more likely to have VDD, underscoring the need for health interventions targeting both obesity and nutrition. Health professionals can help mitigate obesity-related risks by promoting vitamin D screening and encouraging lifestyle changes that improve physical activity and diet. Future longitudinal studies are necessary to confirm causality and develop evidence-based strategies for enhancing pediatric health.